2003
DOI: 10.1242/dev.00509
|View full text |Cite
|
Sign up to set email alerts
|

TheXenopusLIM-homeodomain protein Xlim5 regulates the differential adhesion properties of early ectoderm cells

Abstract: One of the earliest lineage restriction events in embryogenesis is the specification of the primary germ layers: ectoderm, mesoderm and endoderm. In Xenopus, germ layer specification occurs prior to gastrulation and requires the transcription factor VegT both for the cellautonomous specification of endoderm and the generation of mesoderm-inducing signals. In the absence of VegT, ectoderm is formed in all regions of the embryo. In this work, we show that VegT-depleted vegetal cells (prospective endoderm) behave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…In frogs or fish, lhx5 is broadly expressed by early gastrulation stages. Inhibition of Lhx5 function in frogs causes the dissociation of rostral ectodermal cells during gastrulation (Houston and Wylie, 2003), and our studies in zebrafish suggest that Lhx5 regulates Wnt antagonism in the gastrula. In mice, however, no gastrulation defects have been reported in Lhx5 knockout animals (Zhao et al, 1999).…”
Section: Function Of Lhx5 In Vertebrate Developmentsupporting
confidence: 52%
See 1 more Smart Citation
“…In frogs or fish, lhx5 is broadly expressed by early gastrulation stages. Inhibition of Lhx5 function in frogs causes the dissociation of rostral ectodermal cells during gastrulation (Houston and Wylie, 2003), and our studies in zebrafish suggest that Lhx5 regulates Wnt antagonism in the gastrula. In mice, however, no gastrulation defects have been reported in Lhx5 knockout animals (Zhao et al, 1999).…”
Section: Function Of Lhx5 In Vertebrate Developmentsupporting
confidence: 52%
“…Lhx5 belongs to a family of LIM-homeodomain transcription factors, and contains two LIM protein interaction domains and a homeodomain (Hobert and Westphal, 2000;Retaux and Bachy, 2002;Toyama et al, 1995). Previous studies suggested that Lhx5 regulates the differential adhesion of early ectodermal cells in Xenopus (Houston and Wylie, 2003), and morphogenesis and cell proliferation in the mouse hippocampus (Zhao et al, 1999). We show that Lhx5 gain of function in zebrafish inhibits Wnt signaling, whereas inhibition of Lhx5 results in ectopic activation of Wnt signaling and forebrain defects.…”
Section: Introductionmentioning
confidence: 65%
“…Each experiment was repeated a minimum of three times in independent experiments to verify reproducibility of results. Sequences for markerspecific primers are listed in Houston and Wylie (Houston and Wylie, 2003). New primers were generated for NRP-1 (U: 5Ј-TGATCCGCTCTG-CACTCTTT-3Ј, D: 5Ј-TGCTTTGAATTTGCAGTACATTG-3Ј), AP-2 (U: 5Ј-GCAGCCACCAACTCTTCTCT-3Ј, D: 5Ј-CGTAGCTCCATTGCCT-GTTC-3Ј) and Sox-2 (U: 5Ј-TCTGCACATGAAGGAGCATC-3Ј, D: 5Ј-CGTTCATGTGGGCATAAGTG-3Ј).…”
Section: Rt-pcrmentioning
confidence: 99%
“…Cell mixing across this boundary is prevented by expression of surface proteins that control cell position by differential adhesion. Many elements of this model require further testing, including the functional relationship between FoxI1e and other factors known to be important in ectoderm differentiation such as ectodermin (Dupont et al, 2005) Xoom (Hasegawa et al, 2001) and Xlim5 (Houston and Wylie, 2003), as well as the epidermal proteins AP-2 (Luo et al, 2002) and grainyhead-like1 (Tao et al, 2005), and the many early CNS factors including Sox2 and Sox3. It is also likely that there will be signaling pathways in addition to nodals that control the spatial and temporal expression of FoxI1e, and we know little detail concerning its downstream targets.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation